Paclitaxel promotes a caspase 8-mediated apoptosis via death effector domain association with microtubules - Mielgo, Ainhoa (2009)
Microtubule-perturbing drugs have become front line chemotherapeutics, inducing cell cycle crisis as a major mechanism of action. However, these agents exhibit pleiotropic effects on cells, and can induce apoptosis via other means. Paclitaxel, a microtubule-stabilizing agent, induces a caspase-dependent apoptosis, though the precise mechanism(s) remain unclear. Here, we used genetic approaches to evaluate the role of caspase 8 in paclitaxel-mediated apoptosis. We observed that caspase 8-expressing cells are more sensitive to paclitaxel than caspase 8-deficient cells. Mechanistically, caspase 8 was found associated with microtubules, and this interaction increased following paclitaxel-treatment. The prodomains (DEDs) of caspase 8 were sufficient for interaction with microtubules, but the caspase 8 holoprotein was required for apoptosis. DED-only forms of caspase 8 were found in both primary and tumor cell lines, associating with perinuclear microtubules and the centrosome. Microtubule-association, and paclitaxel-sensitivity, depends upon a critical lysine (K156) within a microtubule-binding motif (KLD) in DED-b of caspase 8. The results reveal an unexpected pathway of apoptosis mediated by caspase 8.